Effect of immersion on ground reaction force and contact time during drop jump exercise - Ruschel C.* (2016)
© 2016 National Strength and Conditioning Association.This study analyzed the effect of water immersion on vertical ground reaction force (GRF) peaks and contact times during the braking, propulsion, and landing phases of drop jumps (DJs). Twenty-five healthy male athletes of volleyball and track and field (age 18.0 6 2.4 years) participated in this study. Peak vertical GRF during braking, propulsion, and landing phases; time duration of braking and propulsion phases; and total contact time were measured during maximum DJs performed on land and in water at 4 levels of immersion (tibia, knee, thigh, and hip). A force plate was used to collect GRF data, and the braking and propulsion phases of contact were determined by using an electrical goniometer placed on subject’s knee. The effect of immersion level on variables was analyzed through the use of a repeated measures analysis of variance (p # 0.05). The results showed that increasing immersion leads to a decrease in peak force during the braking phase, landing phase, and in the propulsion phase of the DJ, with the decrease in peak forces between immersions being greater as the immersion level gets deeper. Concerning the contact times, increasing immersion levels caused an increase in total contact time and in the duration of the braking phase. No differences were found for the duration of the propulsion phase between the conditions. Our results have shown that temporal features of the DJ were not preserved in water, and this must be taken into account when choosing the aquatic environment as an alternative for plyometric training. If the rationale of performing plyometric training in water is the reduction of GRFs, then hip immersion seems to offer an interesting combination of significantly lower GRF but without further modification of important temporal features when compared with the other water conditions analyzed.